The Influence of Knowledge to Handwashing Behavior in The Prevention of Covid-19: Pengaruh Pengetahuan terhadap Perilaku Cuci Tangan dalam Pencegahan Covid-19 - Nana Novariana (Journal for Quality in Public Health, 2020)
Covid-19 (Corona Virus Disease 2019) is a group of viruses that can cause diseases in both animals and humans. Some types of Covid-19 are known to cause infections of the respiratory tract in humans ranging from cough, flu, to more serious such as Middle East Respitory syndrome (MERS) and Severe acute respitory syndrome (SARS). It was detected from the first time in December 2019 in Wuhan, Hubei Province, China. According to the data from Lampung Health Ministry, as of 30 May 2020, Lampung had recorded as many as 20 suspected patients, 8 persons died and 2 probable patients and 131 confirmed patients. One of the ways to prevent the spread of Covid-19 is by washing hands by using soap. The purpose of this research is to determine whether the extent of the knowledge may influence the behavior of handwashing by using soap to prevention of Covid-19. The research was conducted by using analytical surveys with cross sectional research design. The population is a community in the work area of Publich Health Center in Panjang, consisting of 1197 families. The samples taken were 307 families by using simple random sampling. Based on the results of the Chi Squre obtained, the results of knowledge of the hand washing behavior of soap-wearing in the prevention of Covid-19 has showed significant results (p = 0.000 OR = 4.11). Conclusio obtained from the study shows the result that there is a significant relationship between the knowledge and the behavior of handwashing by using soap to the spread of disease Covid-19. Namely, with the low awareness of people to wash hands with soap before eating or drinking activities and others, it causes the incidence of high occurrence of Covid-19 disease in Bandar Lampung especially in the area of Publich Health Center in Panjang district.